2023
DOI: 10.1017/s0016756823000717
|View full text |Cite
|
Sign up to set email alerts
|

How old is the Ordovician–Silurian boundary at Dob’s Linn, Scotland? Integrating LA-ICP-MS and CA-ID-TIMS U-Pb zircon dates

Hector K. Garza,
Elizabeth J. Catlos,
Kevin R. Chamberlain
et al.

Abstract: Sedimentary rocks exposed at Dob’s Linn, Scotland, have significantly influenced our understanding of how life evolved over the Ordovician to Early Silurian. The current interpreted chronostratigraphic boundary between the Ordovician and Silurian periods is a Global Boundary Stratotype Section and Point (GSSP), calibrated to 443.8 ± 1.5 Ma (Hirnatian–Rhuddanian age), based on biostratigraphic markers, radioisotopic dates and statistical modelling. However, challenges arise due to tectonic disturbances, complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…LA-ICP-MS U-Pb zircon geochronology allows in situ grain spatial resolution [29] and high single grain resolution throughput (usually >100 grains per sample analysis), which is required for (a) dating complex zircons, (b) detrital studies, and (c) accurately dating bentonites with a potential detrital or xenolith component. Determining crystallization/eruption or maximum deposition age "calls" from LA-ICP-MS U-Pb zircon data are complicated by potential undetermined Pb loss for young zircons (<~400 Ma), matrix mismatch, and large N analysis resulting in apparently robust populations of younger grains that are just an artifact of instrumental statistical spread [30][31][32].…”
Section: Radiometric Data From Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…LA-ICP-MS U-Pb zircon geochronology allows in situ grain spatial resolution [29] and high single grain resolution throughput (usually >100 grains per sample analysis), which is required for (a) dating complex zircons, (b) detrital studies, and (c) accurately dating bentonites with a potential detrital or xenolith component. Determining crystallization/eruption or maximum deposition age "calls" from LA-ICP-MS U-Pb zircon data are complicated by potential undetermined Pb loss for young zircons (<~400 Ma), matrix mismatch, and large N analysis resulting in apparently robust populations of younger grains that are just an artifact of instrumental statistical spread [30][31][32].…”
Section: Radiometric Data From Study Areamentioning
confidence: 99%
“…Furthermore, these dual-technique studies have demonstrated that selecting the LA-ICP-MS U-Pb zircon youngest statistical population (YSP), which is the weighted mean of the youngest statistical population (2 or more grains) that produces a mean square weighted deviation (MSWD) close to 1, approximates CA-ID-TIMS U-Pb zircon results from the same sample [35,36]. A variation of this approach is the youngest mode weighted mean (YMWM), which uses the LA-ICP-MS zircon dates that define the youngest age mode from a kernel density estimate peak that consists of at least three grains that overlap at 2 sigma uncertainty with an MSWD that approximates 1 [32,34]. We use a modified version of the YSP and YMWM age determinations by utilizing an iterative approach that captures the largest population of young grains that overlap at 2 sigma uncertainty with an MSWD that approximates 1.…”
Section: Radiometric Data From Study Areamentioning
confidence: 99%